Cost-effectiveness of generic celecoxib in knee osteoarthritis for average-risk patients: a model-based evaluation. Issue 5 (May 2018) - Losina, E.; Usiskin, I.M.; Smith, S.R.; Sullivan, J.K.; Smith, K.C.; Hunter, D.J.; Messier, S.P.; Paltiel, A.D.; Katz, J.N.
Summary: Objective: The cost-effectiveness of the recently-introduced generic celecoxib in knee OA has not been examined. Method: We used the Osteoarthritis Policy (OAPol) Model, a validated computer simulation of knee OA, to evaluate long-term clinical outcomes, costs, and cost-effectiveness of generic celecoxib in persons with knee OA. We examined eight treatment strategies consisting of generic celecoxib, over-the-counter (OTC) naproxen, or prescription naproxen, with or without prescription or OTC proton-pump-inhibitors (PPIs) to reduce gastrointestinal (GI) toxicity. In the base case, we assumed that annual cost was 130 for OTC naproxen, 360 for prescription naproxen, and 880 for generic celecoxib. We considered a willingness-to-pay threshold of 100, 000 per quality-adjusted life year (QALY) and discounted costs and benefits at 3% annually. In sensitivity analyses we varied celecoxib toxicity, discontinuation, cost, and pain level. Results: In the base case analysis of the high pain cohort (WOMAC 50), celecoxib had an incremental cost-effectiveness ratio (ICER) of 284, 630/QALY compared with OTC naproxen. Only under highly favorable cost, toxicity, and discontinuation assumptions (e.g., annual cost below 360, combined with a reduction in the cardiovascular (CV) event rates below baseline values) was celecoxib likely to be cost-effective. Celecoxib might also be cost-effective at an annual cost of 600 if CV toxicity were eliminated completely. In subjects with moderate pain (WOMAC 30), at the base case CV event rate of 0.2%, generic celecoxib was only cost-effective at the lowest plausible cost (190). Conclusion: In knee OA patients with no comorbidities, generic celecoxib is not cost-effective at its current price.